Angiotensinogen – a marker of non-developing pregnancy - A. A. Orazmuradov; Zh. Zh. Suleymanova; E. A. Kuzmina; I. N. Kostin; Kh. Haddad; E. V. Mukovnikova (Медицинский вестник Юга России, 2025)
Objective: to investigate the effects of angiotensinogen on the endometrium in missed abortion. Materials and methods: a prospective cohort that included 212 women, 160 with missed abortion and 52 with progressing pregnancies at 6–12 weeks. In all participants, the average serum concentration of angiotensinogen was measured. Additionally, a morphological examination of the endometrium was performed in patients with missed abortion. Results: women with missed abortion had significantly lower angiotensinogen levels compared to those with progressing pregnancies. Based on the results of a nonparametric analysis, there was a direct correlation between low angiotensinogen levels and spiral artery thrombosis in missed abortion patients at 11–12 weeks (r=0,37, p<0,01). Conclusion: these findings suggest that a decrease in angiotensinogen levels is associated with impaired angiogenesis in the endometrium and can lead to spiral artery thrombosis during on the endometrium in missed abortion.